X-ray Protection Using Mixture of Cement Shielding with Barium Sulfate - Naji, Abdullah T.; Jaafar, Mohamad S.; Ali, Esmail A. (University of Science and Technology, Yemen, 2015)
This study aims to investigate a way to reduce transmitted x-ray through cement shielding. A cement shielding which painted by Barium Sulfate capable of absorbing a significant portion of X-ray was used with different thickness and composition. The measurements were recorded at various applied voltages (50 kVp to 120 kVp), and the transmitted and backscattered x-ray was measured using ion chamber. The results showed that the cement shielding painted by Barium Sulfate was very effective in the absorption of incident x-ray up to about 95%, and has the ability to reduce backscattered x-ray radiation up to about 75 % by using fabricated iron steel grid based on a plate composed from cement shielding painted by Barium Sulfate.